Craft O'Borneo / Bellona Joseph ... [et al.] - Joseph, Bellona; Joseph, Avellia; Luin, Amy Ann; Elima, Sharel Ashley; Zulkifli, Nadiah; Junaidi, Joyce (2015)
To promote, develop, improve and encourage tourism, tourist trades and all other means and ways of attracting tourists, travelers and others to Sabah Borneo in particular, and to Malaysia in general. To encourage, persuade and advice residents of other states in Malaysia and residents of neighboring countries and elsewhere to spend their holidays in Sabah. To promote the demand for O'Borneo handicrafts and other products made in Sabah.